2013
DOI: 10.1111/clr.12313
|View full text |Cite
|
Sign up to set email alerts
|

Osteotome sinus floor elevation with and without grafting: an animal study in Labrador dogs

Abstract: Spontaneous new bone formation and better bone-to-implant contact were found for OSFE without grafting. The grafting material application during OSFE procedure showed no advantages in histological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…Moreover, another study reported similar endo‐sinus bone gain regardless of the procedure with or without grafting at the 3‐year examination . The result was also in line with a recently published animal study . It was reported that the remodeling of graft apical to implants was observed during the healing period, and the application of grafting materials showed no advantages of endo‐sinus bone gain in histological results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, another study reported similar endo‐sinus bone gain regardless of the procedure with or without grafting at the 3‐year examination . The result was also in line with a recently published animal study . It was reported that the remodeling of graft apical to implants was observed during the healing period, and the application of grafting materials showed no advantages of endo‐sinus bone gain in histological results.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have indicated that the ESBG was significantly correlated with penetration implant lengths. The space below the sinus membrane created by the penetrated implants could help to gain new bone …”
Section: Discussionmentioning
confidence: 99%
“…A recent animal study reported the percentage of bone‐implant contact and bone density for implants placed using OSFE with and without grafting. After 24 weeks, these values were higher for implants placed without grafting; the histological results were identical for both groups of implants . OSFE without grafting provides good stability in terms of endo‐sinus bone levels.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 weeks, these values were higher for implants placed without grafting; the histological results were identical for both groups of implants. 33 OSFE without grafting provides good stability in terms of endo-sinus bone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous bone formation in the elevated area could be observed in both clinical and animal studies (Si et al. , ).…”
mentioning
confidence: 99%